Digital Platforms for Small and Medium-Sized Enterprises: Some Practical Implications - Imaduddin, Imaduddin; Jufriadi, Jufriadi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
This study generally describes the usefulness of digital platforms for small and medium-sized micro-enterprises in Makassar city. This research was carried out by the SMEs sector of Makassar City with Snowball Sampling techniques. Data collection methods are observation methods, in-depth interview methods, and documentation. This qualitative study uses a triangulation model that combines interview and observation methods for small and medium-sized micro-enterprises. The results prove that digital platforms make it easier for SME players to provide information and interact directly with consumers, expand market reach, and increase awareness and sales for SMEs.